Public Opinion about Water Availability - Tatiana Borisova; Damian Adams (EDIS)
This 8-page fact sheet summarizes results of a public survey about Florida water resources. The respondents were asked about the quantity of water in their area, water availability in ten years, the likelihood of prolonged drought, and the effect of climate change on rainfall. Written by Tatiana Borisova and Damian Adams, and published by the UF Department of Food and Resource Economics, March 2012.